A Case of Cerebral Toxoplasmosis and Cryptococcosis Preferred Therapy Associated Adverse Drug Reactions in a Patient Newly Co-diagnosed with Acquired Immune Deficiency Syndrome - Suryawanshi, Vaibhav R.; Purandare, Bharat; Rege, Sujata; Panda, Bijoy Kumar (Current Drug Safety, 2023)
Purpose: The simultaneous occurrence of cerebral toxoplasmosis and cryptococcosis is rare. The infections continue to be treated with sulfadiazine and amphotericin-B-based regimens (preferred therapy), respectively. Both these drugs are linked to some serious adverse drug reactions (ADRs). We report such a unique instance of both; the CNS co-infections and adverse drug reactions to the preferred therapy. Case Presentation: A 44-year-old Asian-Indian female was diagnosed with cerebral toxoplasmosis, impending cryptococcal meningoencephalitis, and acquired immune deficiency syndrome (AIDS). The preferred therapy of opportunistic CNS co-infections commenced. Within a week, she had an occurrence of fall in hemoglobin concentrations (11.3 g/dL to 5.6 g/dL; grade IV), reticulocytosis (1% to 3.2%), and indirect hyperbilirubinemia (0.5 mg/dL to 2.8 mg/dL; grade IV) after sulfadiazine administration. The drug was discontinued and the patient was treated with hematocrit transfusions. After amphotericin-B deoxycholate (AmBd) administration, the patient developed hypokalemia (serum potassium; 4.5 mmol/L to 2.7 mmol/L) and increased serum creatinine (1.0 to 2.2 mg/dL; stage-I) levels. Hence, AmBd was discontinued and potassium correction was given. The patient got diagnosed with sulfadiazine induced hemolytic anemia and AmBd induced acute renal failure. He was switched to alternative therapy regimens for the treatment of cerebral toxoplasmosis and cryptococcosis. Radiological investigations were followed up to confirm the clinical outcomes of alternative therapy. Complete recovery from the ADRs and opportunistic infections was observed. Conclusion: The preferred therapy regimens for toxoplasmosis and cryptococcosis are accompanied by potential adverse drug reactions, thus continuous monitoring is vital, especially in the initial phases of therapy. Discontinuation of the treatment should be the preliminary intervention in the management. Having said that, alternative therapy regimens had an optimal clinical response in the present case.
Keywords: HIV/AIDS